Implementation of Independent Curriculum Material for Phase B Class IV Bhinneka Tunggal Ika: Knowing Indonesian Nation toward Forming Global Diversity Character Students of SDN 210 Babakan Sinyar - Larastuti, Larastuti; Reviyanti, Lysda; Gumilar, Muhammad Ramdan; Rahayu, Ayu Sugiarti (Journal of Education Method and Learning Strategy, 2024)
Indonesia's rich and diverse cultural diversity is an important basis for forming student character. The Merdeka curriculum, with the material "Unity in Diversity: Get to Know the Indonesian Nation", is designed to teach the values of diversity from an early age. This research focuses on the implementation of this material in class IV D of SDN 210 Babakan Sinyar to form a globally diverse character in students. The aim of this research is to analyze how the implementation of the material "Unity in Diversity: Get to Know the Indonesian Nation" can improve students' understanding and attitudes towards diversity, as well as identifying challenges and obstacles faced in the learning process. This research uses descriptive qualitative methods. Data was collected through interviews with teachers and students, learning observations, as well as analysis of curriculum documents and learning implementation plans (RPP). The research subjects were Mrs. Ayu Sugiarti Rahayu, class IV D teacher, and 20 class IV D students at SDN 210 Babakan Sinyar. Research Results: Implementation of the material "Unity in Diversity: Get to Know the Indonesian Nation" shows significant effectiveness in increasing students' understanding of national diversity. Active and collaborative learning methods, such as group discussions, educational games, and group presentations, enable students to internalize the concept of Bhinneka Tunggal Ika well. The results of formative and summative evaluations show that the majority of students are able to apply diversity values in daily interactions, showing increased attitudes of tolerance and respect for differences. Challenges and Obstacles: The main challenges in this learning include limited time in the curriculum, lack of adequate supporting resources, and differences in students' cultural and social backgrounds. In remote areas, access to technology and information is still an obstacle, and the perception that parents do not fully understand the importance of education about cultural diversity is also an obstacle. Strategies to Overcome Challenges: The strategies implemented include integrating material into other subjects, using information and communication technology (ICT) in learning, as well as increasing parental and community involvement in supporting diversity education. Conclusion: Learning Bhinneka Tunggal Ika material has a positive impact on the formation of a globally diverse character in students. Students show increased attitudes of tolerance, empathy and a sense of belonging to Indonesia's diversity. This learning helps students understand that diversity is a national asset that must be protected and appreciated. Collaboration between schools, families and communities is the key to success in achieving this educational goal.